Photo‐Induced Functionalization of para‐Benzoquinones: Access to Dihydroquinoxalines with a Tetrasubstituted Carbon Stereocenter. Issue 6 (14th March 2023) - Dixit, Vikas; Sharma, Arun; Jangid, Aditya; Jain, Nidhi
Abstract : Visible light induced activation of para ‐benzoquinone, and its sequential coupling with alkynes and ortho ‐phenylenediamines/ ortho ‐aminophenols is reported. The protocol provides a route for synthesizing value‐added quinoxaline derivatives with tetrasubstituted carbon stereocenter at room temperature in 36–75% yields. Mechanistic investigation suggests that the reaction proceeds via in‐situ generation of para ‐quinone methide through direct excitation of para ‐benzoquinone in blue light.